Pediatric syncope: pearls and pitfalls in history taking - Jung Sook Yeom; Hyang-Ok Woo (The Korean Pediatric Society, 2023)
Syncope is a heterogeneous syndrome with complex underlying mechanisms, hence, the spectrum of patients presenting with syncope is broad. The diagnosis of syncope begins with history taking, and an accurate diagnosis can be established through correct history taking and interpretation. Building and interpreting patient history are the main factors that cause a diagnostic yield gap between experts and nonexperts. The most frequent source of error is a clinician's misconception rather than an inaccurate account of patient symptoms. Clinicians can have several diagnostic pitfalls while evaluating patient history, which can be avoided by in-depth understanding of the link between syncope pathophysiology and clinical clues. Furthermore, clinicians need to understand the clinical features of diseases that require differentiation from syncope, such as seizures. The use of confusing terms is one of the barriers that prevents accurate diagnosis and communication between doctors and patients. In this review, we address the terms of syncope and its essential history-taking components in connection with the mechanism of syncope.